Transcription of Clostridium thermocellum endoglucanase genes celF and celD. - Mishra, S (1991)
Transcripts of the Clostridium thermocellum endoglucanase genes celF and celD, encoding endoglucanases F and D, respectively, were characterized. The size of the mRNAs was about 2.35 kb for celF and 2.1 kb for celD, indicating monocistronic transcription of both genes. A unique 5' end, located 218 bp upstream from the initiation codon, was found for celF mRNA. No convincing homology could be identified between the sequence upstream from the celF 5' end and other procaryotic promoters. Two 5' ends, located 124 and 294 bp upstream from the initiation codon, were mapped for celD mRNA. The -10 and the -35 sequences preceding the ATG-distal 5' end of celD mRNA were homologous to the consensus sequence of Bacillus subtilis sigma 43 promoters. The sequence upstream from the ATG-proximal 5' end had some similarity with the -10 sequence of B. subtilis sigma 28 promoters. During growth on cellobiose, the 5' end of celD transcripts was found predominantly at the -124 site during the late exponential phase but almost exclusively at the -294 site during the early stationary phase. The kinetics of appearance of celA, celC, celD, and celF mRNA was followed by dot blot analysis. Transcripts of celA, celD, and celF were detected during late exponential and early stationary phase. In contrast, the celC transcript was detected almost exclusively during early stationary phase. Since growth was limited by the availability of cellobiose, the results suggest that the genes are regulated by a mechanism analogous to catabolite repression.